AN ECONOMIC VALUATION OF MARIKINA CITY LIBRARY USING REVEALED PREFERENCE METHODS - Obal, Manilyn P. (Journal of Philippine Librarianship; Vol 35 (2015), 2016)
To address the increasing demand for public libraries to redefine their values and justify their existence in this Digital Age, this study focused on one of the public libraries in the Philippines, the Marikina City Library (MCL) and the estimation of its Total Economic Value (TEV). The TEV of MCL was estimated using an economic-value measurement model that was adapted based on Revealed Preference Theory, which asserts that a person’s preferences can be deduced from his/her behavior and actual choices.
Keywords: public libraries, Marikina City Library, total economic value, economic valuation